Gender, Social Ties, And Reentry Experiences - Scroggins, Jennifer Rhiannon (2012)
A great deal of research has been conducted on factors associated with successful prisoner reentry. However, except for a few studies on women's reentry, most studies have failed to examine the role of parolees' social ties in contributing to reentry outcomes. Additionally, most studies on prisoner reentry only focused on male parolees, and few addressed the influence of gender on reentry experiences. Thus, my goal in this dissertation is to understand the influence of gender on male and female parolees' social ties, and how the resources their ties provide shape their reentry experiences. My dissertation research examines men and women’s strong- and weak-tie relationships and the resources available to them via their relationships to understand how these resources shape their reentry experiences. Study data, which were collected from in-depth interviews with fifty men and women under parole supervision, showed that they underwent many changes in their strong- and weak-tie relationships during and after incarceration. Shifts toward closer and more positive relationships with families and the addition of pro-social weak-tie relationships resulted in more tangible and intangible resources that were considered by the men and women as important to their reentry success. Data analysis showed that the relationship patterns experienced by the men and women in the present study were largely consistent with gendered relationship patterns described in the literature, but that patterns of resource availability from their social ties were less consistent with those described in the literature. Findings from the study suggest the influence of gender on men and women's social ties, as reflected in different patterns of strong-tie relationships experienced prior to, during, and after incarceration, and also reveal some similarities between men and women with regard to increases in the number of weak-tie relationships with various pro-social individuals after incarceration. By showing the significant role of social ties, especially strong-ties, in providing tangible and intangible resources to parolees upon their release from prison, this study provides support for social control theory and highlights the importance of helping ex-offenders develop and maintain positive social ties with pro-social individuals to enhance the availability of resources necessary for successful reentry